Promising Markers in the Context of Mesenchymal Stem/Stromal Cells Subpopulations with Unique Properties - Agnieszka Smolinska; Aleksandra Bzinkowska; Paulina Rybkowska; Magdalena Chodkowska; Anna Sarnowska (Stem Cells International)
The heterogeneity of the mesenchymal stem/stromal cells (MSCs) population poses a challenge to researchers and clinicians, especially those observed at the population level. What is more, the lack of precise evidences regarding MSCs developmental origin even further complicate this issue. As the available evidences indicate several possible pathways of MSCs formation, this diverse origin may be reflected in the unique subsets of cells found within the MSCs population. Such populations differ in specialization degree, proliferation, and immunomodulatory properties or exhibit other additional properties such as increased angiogenesis capacity. In this review article, we attempted to identify such outstanding populations according to the specific surface antigens or intracellular markers. Described groups were characterized depending on their specialization and potential therapeutic application. The reports presented here cover a wide variety of properties found in the recent literature, which is quite scarce for many candidates mentioned in this article. Even though the collected information would allow for better targeting of specific subpopulations in regenerative medicine to increase the effectiveness of MSC-based therapies.